Impact of aeroelastic tailoring on flutter performance of variable ribs’ orientation for different wing box model planforms - Chan, Ying Nee (2021)
For over the past decades, the basic layout of the wing-box configuration was found relatively similar and has not been drastically changed. Nevertheless, with recent advancement in additive manufacturing technology, a much complex structural design can now be manufactured with an efficiency that cannot be acquired by the conventional manufacturing process. From the conducted literature reviews, the variable ribs’ orientation concept turns out to be one of the possible options whereby several previous studies have shown that significant improvement in aeroelastic characteristics can be acquired without any increment in weight. Nevertheless, the previous works were limited to an equally ribs spacing as well as for a certain type of wing-box planforms. Hence, the current effort is to provide a much wider overview on this concept by considering a various type of wing-box planforms including the case of increasing rib’s spacing. Three variants of wing-box planforms were considered in the current work, namely untapered-unswept, untapered-sweptback, and tapered-sweptback configurations. In addition, an equal and increasing rib’s spacing arrangement for a total of 10 and 13 ribs were also taken into account. A programming routine was developed and integrated with the finite element solver, hence allowing the parametric study to be conducted in a much systematically manner. Finite element solutions of flutter analysis and normal mode analysis have been employed, with the flutter speed parameter serves as a sole cost function for the parametric investigation. Further insight was also made with respect to the variation in modal characteristics as well as the distribution in strain energy. The finding shows that the variable ribs’ orientation concept enables significant impact to any modes that incorporate with torsional characteristic, regardless of whether it is dominant or subdominant in torsional shape. As a result, the frequency gap between the flutter modes can be altered hence enables the possibility to further delay the flutter speed. Significant improvement in flutter speed was acquired within a range of 91%-93% for untapered-unswept cases, 78%-92% for untapered-sweptback cases and 56%-78% for tapered-sweptback cases when compared to their respective baseline wing-box planforms. In addition, it was also found that for all the considered cases, the optimal rib’s orientations were characterized by a zigzag profile.